Role of ChatGPT in Undergraduate Education: Benefits, Challenges, and Ethical Considerations - Mehran, Muhammad; Farooq, Ayesha (Journal of Development and Social Sciences, 2025)
This research focuses on benefits and challenges of using Artificial Intelligence (AI), specifically ChatGPT, in undergraduate education at Government College University Lahore. AI technology is advancing, its use in educational settings has been increasing as well. ChatGPT is a high-level language model tool developed by AI, among the most influential tools of one branch in which Artificial Intelligence tool works. This tool uses a large dataset to create text that other humans have produced and it can be utilized for academic purpose. This research study used quantitative research methodology, questionnaires were distributed to gather information from students. The results show that ChatGPT can be a helpful tool for personalized learning, quick content creation, and easy access to information. At the same time, it presents challenges like cheating, misuse, and unequal access to technology. Future research should focus on how the use of AI tools impacts students’ cognitive development and critical thinking skill, Investigate the long-term effects of AI tools on students’ creative and problem-solving abilities, explore how AI technologies like ChatGPT can be integrated into diverse academic coursework and cultural settings and Study the effects of AI in areas with limited resources and accessibility to educational tools.